Jamski medved z Jelovice - Križnar, Matija (Loški razgledi, 2010)
Jelovica was one of the main sites of ore deposits in the past, where iron orewas soutght in karstic chams, sinkholes and caves. The bones and teeth of pleistocene animals were frequently found during the excavation of ore, most often cave bear, wich was very common in Slovenia. Four teeth from Jelovica, preserved in the paleontological collection of the Slovenian Museum of NaturalHistory, provide rare evidence that these animals lived in Gorenjska. The describes teeth probably belong to the species Ursus ingressus, which can be concluded from the size and morphology of the teeth.
Keywords: paleozoologija; arheološke najdbe; jamski medved; zobje; pleistocen; Jelovica; Slovenia; Slovenija